2016
DOI: 10.1088/0957-4484/27/24/245704
|View full text |Cite
|
Sign up to set email alerts
|

Modification of graphene oxide by laser irradiation: a new route to enhance antibacterial activity

Abstract: The antibacterial activity and possible toxicity of graphene oxide and laser-irradiated graphene oxide (iGO) were investigated. Antibacterial activity was tested on Escherichia coli and shown to be higher for GO irradiated for at least three hours, which seems to be correlated to the resulting morphology of laser-treated GO and independent of the kind and amount of oxygen functionalities. X-ray photoelectron spectroscopy, Raman spectroscopy, dynamic light scattering and scanning electron microscopy (SEM) show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 44 publications
1
38
0
Order By: Relevance
“…Despite the notable progress made in the synthesis of two-dimensional metal chalcogenides, the geometric tailoring of porous WS 2 /WO 3 heterostructure by laser treatment remains unexplored. Laser technique has been demonstrated as an attractive method to easily improve the photocatalytic properties of nanomaterials 27, 28 . The enhanced photocatalytic water splitting activity by laser treated TiO 2 has been reported due to the structure modification under the laser irradiation 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the notable progress made in the synthesis of two-dimensional metal chalcogenides, the geometric tailoring of porous WS 2 /WO 3 heterostructure by laser treatment remains unexplored. Laser technique has been demonstrated as an attractive method to easily improve the photocatalytic properties of nanomaterials 27, 28 . The enhanced photocatalytic water splitting activity by laser treated TiO 2 has been reported due to the structure modification under the laser irradiation 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Several organisms are used as models in toxicological studies (Conte et al, 2016;Copat et al, 2012;D'Agata et al, 2014;De Domenico et al, 2011;Kanold, Wang, Brümmer, & Šiller, 2016;Mazzei et al, 2014;Scuderi et al, 2014;Wang, Jia, Zhu, Zhang, & Wang, 2017;Xiao, Vijver, Chen, & Peijnenburg, 2015), and among these, presently, zebrafish is considered the model organism, best suited, for toxicological testing Buccheri et al, 2016;Pecoraro et al, 2018;Pecoraro, D'Angelo, et al, 2017;Pecoraro, Salvaggio, et al, 2017;Salvaggio et al, 2016;Wang et al, 2011). Different types of parameters are used to evaluate NPs toxicity such as hatching F I G U R E 3 Scanning electron microscopy of the corneal surface reveals the presence of microvilli and microplicae and fingerprintlike structures.…”
Section: Discussionmentioning
confidence: 99%
“…Silver nanoparticles (AgNPs) have a large surface area, which provides the particles with a high surface energy and more reaction sites available than bulk materials. These features make AgNPs a good candidate as a material to be used in catalysis processes (Yu, Yin, & Liu, 2013); nanosilver has also proved to be an effective antibacterial (Buccheri et al, 2016;Ju-Nam & Lead, 2008;Kim et al, 2007;Luoma, 2008) and antifungal agent (Kim et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The ability of laser GO reduction allows the facile and non-toxic writing of RGO-GO-RGO patterns in various configurations to build electrical double layer capacitor or supercapacitors [13]. In [14] authors demonstrated the enhancement of antibacterial activity of laser irradiated graphene oxide in dependence on the experimental parameters (GO concentration, irradiation conditions).…”
Section: Introductionmentioning
confidence: 99%